A French-speaking speech-language pathology program in West Africa: Transfer of training between Minority and Majority World countries. (February 2013) - Topouzkhanian, Sylvia; Mijiyawa, Moustafa
Abstract: In West Africa, as in Majority World countries, people with a communication disability are generally cut-off from the normal development process. A long-term involvement of two partners (Orthophonistes du Monde and Handicap International) allowed the implementation in 2003 of the first speech-language pathology qualifying course in West Africa, within the Ecole Nationale des Auxiliaires Medicaux (ENAM, National School for Medical Auxiliaries) in Lome, Togo. It is a 3-year basic training (after the baccalaureate) in the only academic training centre for medical assistants in Togo. This department has a regional purpose and aims at training French-speaking African students. French speech-language pathology lecturers had to adapt their courses to the local realities they discovered in Togo. It was important to introduce and develop knowledge and skills in the students' system of reference. African speech-language pathologists have to face many challenges: creating an African speech and language therapy, introducing language disorders and their possible cure by means other than traditional therapies, and adapting all the evaluation tests and tools for speech-language pathology to each country, each culture, and each language. Creating an African speech-language pathology profession (according to its own standards) with a real influence in West Africa opens great opportunities for schooling and social and occupational integration of people with communication disabilities.